2022
DOI: 10.3390/antiox11081449
|View full text |Cite
|
Sign up to set email alerts
|

5G Electromagnetic Radiation Attenuates Skin Melanogenesis In Vitro by Suppressing ROS Generation

Abstract: Recently, the impacts of 5G electromagnetic radiation (EMR) with 28 GHz on human health have been attracting public attention with the advent of 5G wireless communication. Here, we report that 5G (28 GHz) EMR can attenuate the skin pigmentation in murine melanoma cells (B16F10) and a 3D pigmented human epidermis model (Melanoderm™). B16 cells were exposed to 5G (28 GHz) with or without α-MSH for 4 h per day. Interestingly, 5G attenuated α-MSH-induced melanin synthesis. Fontana–Masson staining confirmed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…In HaCat human keratinocytes, Kim et al ( 2021) reported that a 1.76 GHz RF-EMF exposure at 4 W/kg, 2 h per day for 4 days, induced intracellular ROS production (Kim et al, 2021). The same author also shown a reduction in the ability of α-melanocytestimulating hormone to induce melanogenesis through decreased ROS level, in B16F10 murine melanoma cells exposed for 4 h per day up to 2 days to CW 28 GHz signal at 10 W/m 2 (Kim et al, 2022). Those data in the human HaCat cell line are thus contradictory and also in contrast with our findings.…”
Section: Discussionmentioning
confidence: 98%
“…In HaCat human keratinocytes, Kim et al ( 2021) reported that a 1.76 GHz RF-EMF exposure at 4 W/kg, 2 h per day for 4 days, induced intracellular ROS production (Kim et al, 2021). The same author also shown a reduction in the ability of α-melanocytestimulating hormone to induce melanogenesis through decreased ROS level, in B16F10 murine melanoma cells exposed for 4 h per day up to 2 days to CW 28 GHz signal at 10 W/m 2 (Kim et al, 2022). Those data in the human HaCat cell line are thus contradictory and also in contrast with our findings.…”
Section: Discussionmentioning
confidence: 98%
“…Possible negative effects have been observed on memory (Qin et al, 2022), cellular function (Cui et al, 2017), the immune (Benavides et al, 2023) and nervous systems (Chen et al, 2021), and sleep quality. However, positive effects have also been observed in the application of electromagnetic radiation in neuronal survival and differentiation (Urnukhsaikhan et al, 2016) and in the prevention of melaninrelated diseases (Kim et al, 2022). These discrepant results are sometimes explained by different frequencies and/or exposure settings applied to biological models.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies are being carried out to investigate effects of the fifth generation (5G) wireless communication on the human body since the 5G commercial service has started [1][2][3][4][5][6][7]. Especially for the 5G service using mmWave, human body exposure to electromagnetic fields (EMFs) from a base station is one of major concerns because base stations generate sharp beams and steer beams directly to 5G service users.…”
Section: Introductionmentioning
confidence: 99%
“…The sharp beam results in a high power density (PD) to be exposed to the human body while the beam steering increases the possibility of such high-PD exposure. In [5], the mmWave exposure is studied in a cell level by exposing the cultured cells to the mmWave EMF. Refs.…”
Section: Introductionmentioning
confidence: 99%